Pengaruh Profitabilitas, Leverage, Dan Sales Growth Terhadap Tax Avoidance - Fitriani, Savira Nur; Suhono,; Wiliyanti, Rizke; Miharja, Rediawan (The Double Entry Journal, 2022)
This study aims to determine the effect of profitability, leverage, and sales growth on tax avoidance. This research using all manufacturing companies subsector food and beverage consumption listed on the Indonesia Stock Exchange as population. Samples were selected using purposive sampling method periode 2016 – 2020. Data analysis techniques in this study are descriptive and verification analysis. Hypothesis testing using linier regression test using SPSS 21. This results were indicate that profitability has no effect on tax avoidance, leverage has no effect on tax avoidance, and sales growth has no effect on tax avoidance.